Computational structure-based design of antiviral peptides as potential protein–protein interaction inhibitors of rabies virus phosphoprotein and human LC8 - Saman Rahmati; Fatemeh Zandi; Khadijeh Ahmadi; Ahmad Adeli; Niloofar Rastegarpanah; Massoud Amanlou; Behrouz Vaziri (Heliyon)
Rabies is a serious zoonotic disease caused by the rabies virus (RABV). Despite the successful development of vaccines and efforts made in drug discovery, rabies is incurable. Therefore, development of novel drugs is of interest to the scientific community. Antiviral peptides can be designed based on the known structures of viral proteins and their biological targets. Cytoplasmic dynein light chain LC8, one of the first identified host partners of RABV phosphoprotein (RABV P), is an essential factor for RABV transcription and replication. As part of the search for new potential drugs against rabies, we used structure-based drug design using the in silico tools. The binding site of LC8 with RABV P was used for peptide design. Four potential peptide inhibitors (Pep1-4) were selected, modeled, and docked with RABV P. The highest binding affinity was observed for the RABV P-Pep2 complex. Molecular dynamics (MD) simulations were performed and the stability of the peptides and complexes was confirmed. Finally, Pep2 can be used as a potential candidate for peptide-based antiviral therapy against RABV. The identified small peptides may prevent RABV infection based on the results of the current investigation. Further in vitro and in vivo studies are needed to confirm these results.